6(2+6k)-8=-176

Simple and best practice solution for 6(2+6k)-8=-176 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2+6k)-8=-176 equation:


Simplifying
6(2 + 6k) + -8 = -176
(2 * 6 + 6k * 6) + -8 = -176
(12 + 36k) + -8 = -176

Reorder the terms:
12 + -8 + 36k = -176

Combine like terms: 12 + -8 = 4
4 + 36k = -176

Solving
4 + 36k = -176

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 36k = -176 + -4

Combine like terms: 4 + -4 = 0
0 + 36k = -176 + -4
36k = -176 + -4

Combine like terms: -176 + -4 = -180
36k = -180

Divide each side by '36'.
k = -5

Simplifying
k = -5

See similar equations:

| -(b-5)=b-3 | | -3(-2+x)=-10 | | -11+a=-2(7a-2) | | 19r=-57 | | x^2+(1-i)x-i=0 | | -4v+2(-1-6v)=-130 | | -2(2y-6)-y=-2(y-3) | | 2a-4=3(a-4) | | x^2+(1-i)x-1=0 | | 2(2y-1)=-19 | | -32+8v=6(v-7) | | 2b^2+3b-2= | | -42=3(6+8b)+6(-3b-7) | | 9x-2=133 | | 60=-5(6n-6) | | 38-n=5+4(-2n+3) | | -26+6p=-8(1-3p) | | 2(r+4)=-35 | | 580=-20b | | 9y+12=84 | | 21x-3=40x | | 2(3-x)=60 | | -5.5=-3.4 | | 7(x-2)=5(x-4) | | -7(7n+7)=39-5n | | 3+r=19 | | 10b^2-15b-8b+12b=0 | | 12x^4+10x^3-12x^2=0 | | -3n-2(-8n-3)=-14+3n | | 6x+12+54=180 | | 18x+6=19x | | 2(2p-3)=36-2p |

Equations solver categories